A systematic expression analysis implicates Plexin-B2 and its ligand Sema4C in the regulation of the vascular and endocrine system - Zielonka, Matthias; Xia, Jingjing; Friedel, Roland H.; Offermanns, Stefan; Worzfeld, Thomas (Experimental cell research, 2010)
Plexins serve as receptors for semaphorins and play important roles in the developing nervous system. Plexin-B2 controls decisive developmental programs in the neural tube and cerebellum. However, whether Plexin-B2 also regulates biological functions in adult nonneuronal tissues is unknown. Here we show by two methodologically independent approaches that Plexin-B2 is expressed in discrete cell types of several nonneuronal tissues in the adult mouse. In the vasculature, Plexin-B2 is selectively expressed in functionally specialized endothelial cells. In endocrine organs, Plexin-B2 localizes to the pancreatic islets of Langerhans and to both cortex and medulla of the adrenal gland. Plexin-B2 expression is also detected in certain types of immune and epithelial cells. In addition, we report on a systematic comparison of the expression patterns of Plexin-B2 and its ligand Sema4C, which show complementarity or overlap in some but not all tissues. Furthermore, we demonstrate that Plexin-B2 and its family member Plexin-B1 display largely nonredundant expression patterns. This work establishes Plexin-B2 and Sema4C as potential regulators of the vascular and endocrine system and provides an anatomical basis to understand the biological functions of this ligand-receptor pair.
Gesehen am 09.02.2024